1999
DOI: 10.1046/j.1365-2699.1999.t01-1-00311.x
|View full text |Cite
|
Sign up to set email alerts
|

An alternative hypothesis for the origin of Amazonian bird diversity

Abstract: AimTo determine the origin of the high diversity of birds and other animals and plants in Amazonia. Previous hypotheses are: palaeogeography hypothesis, river hypothesis, riverrefuge hypothesis, refuge hypothesis, disturbance-vicariance hypothesis, gradient hypothesis, pest-pressure hypothesis, intermediate disturbance hypothesis, riverine disturbance hypothesis, models of fine-scale habitat heterogeneity, lake hypothesis, and museum hypothesis.Methods At present there is agreement between areas of high specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
0
12

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(141 citation statements)
references
References 72 publications
4
125
0
12
Order By: Relevance
“…Nores (1999) has suggested that the high levels of Amazonian bird diversity might be explained by Quaternary and upper Tertiary sea-level rises of up to 100 m that would have fragmented the lower Amazonian environment into numerous islands. Although such sea-level rises may also in part explain the high diversity of the C. cleonus group in the lower Amazon, perhaps the repeated confinement of lower Amazon species to very small areas of higher ground during sea-level rises, and the resulting habitat instability, led to their small current range sizes.…”
Section: Distribution Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nores (1999) has suggested that the high levels of Amazonian bird diversity might be explained by Quaternary and upper Tertiary sea-level rises of up to 100 m that would have fragmented the lower Amazonian environment into numerous islands. Although such sea-level rises may also in part explain the high diversity of the C. cleonus group in the lower Amazon, perhaps the repeated confinement of lower Amazon species to very small areas of higher ground during sea-level rises, and the resulting habitat instability, led to their small current range sizes.…”
Section: Distribution Patternsmentioning
confidence: 99%
“…Hypotheses that have been developed to explain these patterns differ in treating speciation as having occurred in sympatry, parapatry, or allopatry and in their emphasis on which physical or ecological barriers were most important in controlling interbreeding and dispersal. They include the gradient hypothesis (steep environmental gradients; Endler 1977Endler , 1982Mallet 1993), palaeogeography hypothesis (tectonic movements and sea-level rises ;Chapman 1917;Emsley 1965;Frailey et al 1988;Räsänen et al 1995;Webb 1995;Nores * At the request of the authors, publication of this manuscript was postponed to July 2002. 1999), river hypothesis (rivers and their floodplains; Wallace 1852; Capparella 1988Capparella , 1991Ayres and Clutton-Brock 1992), disturbance-vicariance hypothesis (climatic cooling causing ecologically unsuitable habitat; Colinvaux 1993Colinvaux , 1996Colinvaux et al 1996), and refuge hypothesis (reduced precipitation causing forest fragmentation ;Haffer 1969;Simpson and Haffer 1978;Prance 1982a;Whitmore and Prance 1987).…”
mentioning
confidence: 99%
“…2. The Refuge Hypothesis has been investigated by a number of researchers and has been the focus of considerable debate (Brown, 1982;Froehlich et al, 1991;Nores, 1999;Prance, 1982;Prance, 1973;R€ a as€ a anen et al, 1991;Vanzolini, 1970). Duellman (1982) proposed a hypothesis similar to HafferÕs (1969) Refuge Hypothesis, but specific to anurans.…”
Section: Introductionmentioning
confidence: 99%
“…The above geological events we put forward as major vicariant forces driving the speciation among Pteroglossus aracaris are likely to have influenced the evolution of the Neotropical biota with comparable geographic distribution in tropical America (Bush, 1994;Nores, 1999Nores, , 2004Wesselingh and Salo, 2006). Similar patterns of temporal divergence have been independently suggested from molecular data for a growing number of congeneric species, including curassows and piping-guans (Grau et al, 2005;Pereira and Baker, 2004), parrots (Ribas et al, 2007), trogons (Moyle, 2005), monkeys (Collins and Dubach, 2001;Cortes-Ortiz et al, 2003), vesper mice and spiny rats (Galewski et al, 2005;Salazar-Bravo et al, 2001), bats (Lim, 2007;Stadelmann et al, 2007), catfishes (MontoyaBurgos, 2003), and geckos (Gamble et al, 2008).…”
Section: A Biogeographic Hypothesis For the Evolution Of Pteroglossusmentioning
confidence: 93%